Artificial Intelligence in Mechanical Technology: A Leverage for Sustainable Development in the Prevailing Economic Uncertainties in Edo State, Nigeria - Ogbebor, Jehu; Osuyi, S. O. (NIU Journal of Educational Research, 2025)
This study investigated how artificial intelligence in mechanical technology can leverage sustainable development in a period of economic uncertainties in Edo State, Nigeria. Four research questions guided the study and one hypothesis was tested at 0.05 level of significance. The study adopted a descriptive survey research design with a population of 80 respondents, which consisted fifty-three (53) technical teachers from five public technical colleges and twenty-seven (27) managers of mechanical technology industries in Edo State. The entire population was used as the sample because it was of manageable size A structured questionnaire with twenty (20) items arranged in clusters was used as instrument for data collection. The instrument was validated by three experts from the department of Vocational and Technical Education, University of Benin, Benin City. Cronbach alpha statistical formula was used to test the reliability of the instrument and it yielded a coefficient of 0.85. The findings of the study revealed that artificial intelligence in mechanical technology improves learning experience and learning outcome, increases productivity, improves design accuracy, reduces production labour cost, reduces material wastage, saves time and improves environmental health. Based on the findings, it was recommended, amongst others, that artificial intelligence tools should be incorporated into mechanical technology delivery systems in institutions of learning where mechanical technology is offered and in mechanical technology industries for sustainable development under economic uncertainties in Edo State, Nigeria. Keywords: Artificial Intelligence, Mechanical Technology, Economic Uncertainties and Sustainable Development